Inovasi Sistem Informasi STUNEDUCATE sebagai Upaya Meningkatkan Indeks Literasi Stunting Masyarakat Kabupaten Enrekang Sulawesi Selatan - Ismaya Ismaya; Apriyanto Apriyanto; Ushwa Dwi Masrurah Arifin Bando; Andi Ahmad Chabir Galib; Nurmila Ramadani; Suherdiansyah Suherdiansyah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service program aims to provide innovation to the Enrekang Regency Stunting Reduction Acceleration Team (TPPS) in conducting stunting counselling to the Enrekang Community. This service method uses STUNEDUCATE information system training with target partners, namely the Team for the Acceleration of Stunting Reduction (TPPS) of Enrekang Regency, South Sulawesi Province. The evaluation instrument of this activity is a questionnaire and analyzed descriptively. The result of this service activity is the creation of new innovations for TPPS Enrekang Regency in terms of conducting online-based stunting counselling. TPPS can provide stunting education online so that TPPS is no longer constrained by distance and time. With the massive online counselling by TPPS through the STUNEDUCATE information system, the stunting literacy index of the Enrekang Regency Community can be further increased, and the stunting rate can be achieved in accordance with Presidential Regulation Number 72 of 2021 concerning the acceleration of stunting reduction.